HUBUNGAN ANTARA POLA ASUH DAN KEPERCAYAAN DIRI SISWA SMA DI JAKARTA - Angela , Grace; Monika, Monika (Provitae: Jurnal Psikologi Pendidikan, 2024)
Parenting is a parenting pattern given by parents to children to guide children. This study aims to determine the pattern of care given by parents to children allegedly closely related to the belief in the child to do something or what is called the child's self-confidence. The type of research used is this non-experimental quantitative correlational study using purposive sampling techniques with survey methods using two measuring instruments, namely the Personal Evaluation Inventory and the parenting scale developed by Chandra and Suyasa (2006) adaptation of Baumrind's theory (1991) through g-forms. Participants obtained in this study were 311 participants. All data obtained was processed using Statistical Product and Service Solutions (SPSS) using a correlation test. The results showed that there was a positive relationship between parenting style and self-confidence with the results of the correlation analysis showing that mother's parenting style had a strong positive correlation with student self-confidence (r = 0.742), as well as father's parenting style (r = 0.811).